John Locke at the Polish Brothers school - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2020)
The goal of this article is to show the influence of Polish Brothers on the British philosopher John Locke. As an example, it will be point out the influence of Polish Brothers on the very influential text of Locke’s A Letter Concerning Toleration and other writings of this philosopher. Only in recent years it was accepted that Locke borrowed the concepts like tolerance and rationality of religious beliefs from Polish Brothers.